Review of agriculture robotics: Practicality and feasibility - Hajjaj S.S.H.; Sahari K.S.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Agriculture; Computer software reusability; Cost effectiveness; Food supply; Intelligent control; Intelligent robots; Machine design; Mobile robots; Precision agriculture; Robotics; Smart sensors; Cost effective; Food security; Human population; Human robot Interaction (HRI); Operational scale; Research activities; Software sharing; Wireless connection; Human robot interaction